Riscos ocupacionais em uma indústria de utensílios de alumínio: análise do ambiente e condições de trabalho - Mezoni, Maressa Fontana (2021)
The industrial sector, in continuous evolution, demands that its components keep pace. For this, associations in general tend to offer workers an accelerated pace of work, contributing to the emergence of work accidents. In order to verify whether the variables gender, age and length of service in the function appear with occupational accidents, as well as verifying the conditions in the environment / work station and how ergonomic demands of operators in an industry producing elements of In this work, the Research methodology was applied based on the adapted Nasa-TLX Method and the Corlett Pain Diagram, to identify the conditions of the work environment from the perspective of the worker. The collected data were treated using the RStudio Software version 4.0.2, analyzing the statistical treatment aimed at Pearson's Correlation Analysis, to identify which variables are associated with the work indexes, Analysis of Variance to verify the existence of differences between the averages of each analyzed sector and Tukey's Test, for a comparison between the sectors regarding the characteristics related to the noise index in the production line. Confidence Intervals (CI) were determined for variables related to illuminance and temperature indices. The analysis of the work environment showed noise values above the recommended limit, in almost all sectors investigated, the same happening with the illuminance index. In the production line, the temperature was evaluated as high, for the activity performed. Cluster Analysis was used to verify the similarity present in the responses obtained through the questionnaire. In general, complaints of pain during the working day were highlighted by about 51.6% of the sample of 31 operators, who reported pain or discomfort while performing their work activities. The Cluster Analysis showed that three distinct groups were formed: group one characterized by individuals between 18 and 27 years old with little experience in the activity - 42% reported pain or discomfort. Group two, composed of older operators, had the highest incidence of pain or pain as a result of work activity (62%). Group three, the highest incidence of work accidents, composed of young male operators with experience in the function and who consume alcoholic beverages up to three times a week, with an incidence of pain/pain of 50%. The OWAS Method, applied to verify the postures of operators, denoted risks of categories 2 and 3, respectively, for the Conforming and Boxing activities. This study allowed, through the application of the stipulated methodology, to demonstrate that it is possible to identify possible points of failure at an operational level, points that can contribute or cause physical constraints to the worker and even accidents resulting from the execution of the work activity. Furthermore, there was the possibility of getting to know the work environment from the perspective of the operators, as well as the possibility of detailing and analyzing the incidence of pain and pain through a self-perceived diagnosis. This study brings new practical and social contributions to the activity developed aimed at the metalworking sector.